Dynamic disulfide bond-containing glycidyl amine and preparation method thereof, and preparation method of light lightning protection surface film for composite material with self-repairing function

By introducing dynamic disulfide bonded glycidylamine and lightweight conductive filler into the lightning-proof surface film of composite materials, combined with flexible conductive polymer network, the problems of poor conductivity and high repair cost of composite materials are solved, and lightweight , a self-repairable lightning-proof surface film reduces repair costs and improves performance.

CN119306685APending Publication Date: 2025-01-14INST OF PETROCHEM HEILONGJIANG ACADEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411211640.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The composite material has poor conductivity when it is hit by lightning during flight, resulting in structural damage. The existing lightning-proof surface film has a large weight, poor bending resistance and cannot be self-repair, and the repair cost is high.

Method used

Design glycidylamine containing dynamic disulfide bonds and its preparation method, combined with light conductive fillers, flexible conductive polymer mesh and acid anhydride curing agent, and prepared with self-healing by blending, mechanical dispersion, vacuum kneading, and hot-calendering film formation methods Functional lightweight lightning-proof surface film.

Benefits of technology

It has realized structural and functional repair of lightning-proof surface film, with bending resistance and lightweight characteristics, which reduces repair costs, improves adhesive performance and hardness, and can reduce weight by more than 30% per unit area mass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005020455050000021
    Figure BDA0005020455050000021
  • Figure BDA0005020455050000061
    Figure BDA0005020455050000061
  • Figure BDA0005020455050000091
    Figure BDA0005020455050000091
Patent Text Reader

Abstract

The invention discloses glycidyl amine containing dynamic disulfide bonds, a preparation method of glycidyl amine and a preparation method of a light lightning protection surface film with a self-repairing function for a composite material, and belongs to the field of lightning protection surface films for self-repairing composite materials. The specific scheme is as follows: the light lightning protection surface film with the self-repairing function for the composite material comprises glycidyl amine containing dynamic disulfide bonds, a reactive diluent containing epoxy groups, an anhydride curing agent, an inorganic filler, a plasma functionalized light conductive filler, a flexible conductive polymer net and a toughening agent, all the components are prepared through blending, mechanical dispersion, vacuum kneading and hot rolling film forming methods. The prepared light lightning protection surface film with the self-repairing function for the composite material has the advantages of excellent bonding performance, high hardness and light weight, the bonding strength is larger than or equal to 25 MPa, the repairing efficiency is larger than or equal to 90%, and the mass per unit area can be reduced by 30% or above under the same function condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of lightning protection surface films for self-repairing composite materials, and in particular relates to a glycidylamine containing a dynamic disulfide bond and a preparation method thereof, and a preparation method of a lightweight lightning protection surface film for a composite material with a self-repairing function. Background Art

[0002] Composite materials are increasingly widely used in various aerospace vehicles due to their advantages of high specific stiffness, high specific strength, designable performance, fatigue resistance and corrosion resistance, which greatly promotes the lightweight, high performance and structural function integration of aircraft. At the same time, the application parts of composite materials have developed from non-load-bearing parts and secondary load-bearing parts of aircraft to main load-bearing parts, and are developing in the direction of large-scale and integrated. The use of advanced composite materials has become an important symbol of the advancement of aircraft. In recent years, due to the increasing requirements for lightweight aircraft structures, the use of composite materials has also shown an upward trend. The use of composite materials in Boeing 787 aircraft has accounted for 50% of the structural weight, while the use of composite materials in Airbus A350 has reached 52%. Not only has the proportion of composite materials increased sharply, but composite materials are also widely used in the main load-bearing components of aircraft, such as fuselage, wings, center wings, etc. The use of composite materials in my country's civil large aircraft C919 is about 12%. The proportion of composite materials used in helicopters is even higher, up to more than 90%, and even all-composite helicopters have appeared. The rapid development of drones in recent years has also pushed the use of composite materials to a higher level. The extensive application of composite materials in aircraft has brought about another problem that cannot be ignored. Since most composite materials have poor electrical conductivity, they cannot quickly conduct huge current when struck by lightning during flight, causing damage to structural parts, posing a huge threat to the safety of aircraft and passengers. The commonly used method for lightning protection of composite materials is to use lightning protection surface film and prepreg integral molding technology to prepare composite components with lightning protection function. The most important component / component in the lightning protection surface film is the conductive component. The most commonly used one is the metal conductive mesh, and the maturity of other non-metallic conductive components is not high. The lightning protection surface film using the metal conductive mesh faces the following problems: First, the metal mesh is heavy; second, the metal mesh has poor bending resistance, which makes the metal conductive network prone to breakpoints and affects the conductivity; third, after being damaged by mechanical or lightning, the structure and functionality cannot be repaired by themselves, and can only be repaired by replacing parts or more complicated factory digging and repairing technology, which is costly. Summary of the invention

[0003] The purpose of the present invention is to solve the problems of poor bending resistance, inability to self-repair or complex artificial repair process, high repair cost, obvious decrease in lightning protection effect after repair and large unit area mass in the prior art of the lightning protection surface film for composite materials, and further provide a glycidylamine containing dynamic disulfide bonds and a preparation method thereof, and a preparation method of a lightweight lightning protection surface film for composite materials with self-repairing function. The above series of problems can be solved by designing a composite material with dual self-repairing functions with structural integrity and functional integrity for the lightning protection surface film. The present invention is based on the design of a main resin system for dynamic covalent bonds, a conductive network system for highly conductive lightweight carbon-based conductive fillers, and a flexible polymer network for bending-resistant flexible conductive polymer networks. The self-repairing lightning protection surface film designed can achieve structural repair and functional repair of the lightning protection surface film, and has bending resistance and lightweight characteristics. The present invention can improve the process performance of the lightning protection surface film, expand the scope of application in complex components, avoid high-cost repair processes such as digging and repairing damaged lightning protection composite components and replacing damaged components, and has great development prospects and application value in the field of aerospace.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A glycidylamine containing a dynamic disulfide bond, including a substance represented by structural formula I, structural formula II, structural formula III or structural formula IV:

[0006]

[0007]

[0008] A method for preparing a tetrafunctional glycidylamine containing a dynamic disulfide bond comprises the following steps:

[0009] Add epichlorohydrin, deionized water and ethylene glycol to a four-necked flask equipped with a stirrer, a condensing device, a dropping funnel and nitrogen protection, heat it in an oil bath at 40-60°C, add 4,4'-diaminodiphenyl disulfide in 3-5 times, and after adding, control the temperature of the reaction system at 50-70°C for 1-2 hours, then add chloroform and continue stirring for 6-10 hours. Lower the temperature to 30-50°C, slowly and uniformly add a 30%-50% NaOH aqueous solution, and keep warm for 60-150 minutes. After the reaction is completed, cool the reaction mixture to room temperature, add chloroform to the four-necked flask, transfer the reaction solution to a separatory funnel, and wash with deionized water 3-5 times; after standing and stratifying, take the lower layer of solution into a beaker, add anhydrous MgSO 4 , stir for 1 to 3 hours; filter to remove MgSO 4After the solvent is distilled off, the product is separated and purified by silica gel column chromatography, with dichloromethane as the eluent. After the eluent is distilled off, it is vacuum dried for 12 to 24 hours to obtain a tetrafunctional glycidylamine containing a dynamic disulfide bond, as shown in structural formula I. Among them, the molar ratio of 4,4'-diaminodiphenyl disulfide to epichlorohydrin is 1:2; epichlorohydrin, deionized water and ethylene glycol are mixed in any proportion; the ratio of epichlorohydrin to NaOH aqueous solution is 1mol:100-200ml; the ratio of chloroform to epichlorohydrin added twice is 5ml-15ml:1ml; epichlorohydrin and MgSO 4 The ratio is 1ml:3g~6g.

[0010] A method for preparing a lightweight lightning protection surface film for composite materials with self-repairing function, wherein the components of the lightweight lightning protection surface film for composite materials with self-repairing function include glycidylamine containing dynamic covalent bonds, a diluent, an acid anhydride curing agent, an inorganic filler, a lightweight conductive filler, a flexible conductive polymer net and a toughening agent, and the lightweight lightning protection surface film for composite materials with self-repairing function is prepared by blending the components, mechanically dispersing, vacuum kneading, and hot calendering film forming methods. The glycidylamine containing dynamic disulfide bonds includes the substances described in the structural formula I, structural formula II, structural formula III and structural formula IV.

[0011] Furthermore, the mass ratio of the glycidylamine containing dynamic disulfide bonds represented by structural formula I, structural formula II, structural formula III and structural formula IV is 100:5-15:10-20:5-10.

[0012] Furthermore, the diluent is a commercial reactive diluent containing epoxy groups, including diluents HK-66 (alkylene glycidyl ether), 622 (1,4-butanediol diglycidyl ether), 669 (ethylene glycol diglycidyl ether), 690 (phenyl glycidyl ether), X-632 (polypropylene glycol diglycidyl ether), AGE (C12-14 fatty glycidyl ether), 692 (benzyl glycidyl ether), X-652 (1,6-hexanediol diglycidyl ether) and D-691 propylene oxide o-tolyl ether, or a mixture of several thereof, and the amount of the diluent used is 10% to 20% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0013] Furthermore, the anhydride curing agent includes one or a mixture of phthalic anhydride, tetrabromophthalic anhydride, diphenyl ether tetracarboxylic anhydride, succinic anhydride, glutaric anhydride and maleic anhydride.

[0014] Furthermore, the molar ratio of the anhydride curing agent to the epoxy groups in the formulation components is 0.45 to 0.5:1.

[0015] Furthermore, the inorganic filler includes glass flakes and two-dimensional boron nitride nanosheets, and the total amount thereof is 5%-15% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0016] Furthermore, the mass ratio of the glass flakes to the two-dimensional boron nitride nanosheets is 100:10 to 50. The diameter of the glass flakes ranges from 0.1 mm to 0.5 mm, and the thickness ranges from 1 μm to 10 μm. The diameter of the two-dimensional boron nitride nanosheets ranges from 1 μm to 5 μm, and the thickness ranges from 2 nm to 10 nm.

[0017] Furthermore, the light conductive filler is composed of graphene, conductive carbon black and conductive carbon nanotubes, the light conductive filler is surface treated by plasma, and the amount of the light conductive filler is 1%-5% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0018] Furthermore, the mass ratio of the graphene, the conductive carbon black and the conductive carbon nanotubes is 100:10-20:5-15.

[0019] Furthermore, the flexible conductive polymer mesh is a nylon or polyester fabric with a metal-plated surface, and the plated metal includes silver or copper or a mixture of silver and copper in any proportion or a silver-copper alloy or a silver-nickel alloy in any proportion (the mass ratio of silver and nickel is 100:10-20), and the mass per unit area is 50g / ㎡ to 100g / ㎡.

[0020] Furthermore, the toughening agent comprises one or a mixture of polyphenol oxide resin, polysulfone resin, polyether ketone resin and methyl methacrylate-butadiene-styrene copolymer, and the amount used is 10%-20% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0021] Furthermore, the specific steps of preparing a lightweight lightning protection surface film for a composite material with self-repairing function by blending, mechanically dispersing, vacuum kneading, and hot calendering film-forming methods are as follows:

[0022] (1) Preparation of blends

[0023] The toughening agent and the tetrafunctional glycidylamine containing dynamic disulfide bonds shown in structural formula I are added to a chloroform solution, stirred until dissolved and transparent, and the chloroform is removed by rotary distillation to obtain a blend A of the toughening agent and the tetrafunctional glycidylamine containing dynamic disulfide bonds.

[0024] (2) Preparation of lightweight conductive filler and glycidylamine blends

[0025] The light conductive filler is added to the chloroform solution, ultrasonically dispersed for 1 to 3 hours, and glycidylamine containing dynamic disulfide bonds shown in structural formula II to structural formula IV is added, and magnetic stirring is performed for 1 to 3 hours to form a uniform system. The chloroform is removed by rotary distillation to obtain a blend B of the light conductive filler and glycidylamine.

[0026] (3) Preparation of grinding dispersion resin

[0027] A blend B of a light conductive filler and glycidylamine, an anhydride curing agent and an inorganic filler are mixed to form a coarse mixture C, and the coarse mixture C is ground and dispersed on a CNC three-roll grinder for 3 to 5 times to obtain a ground and dispersed resin D. The roller surface temperature of the three-roll grinder is controlled within a range of 20 to 50°C.

[0028] (4) Preheat blend A in a blast drying oven for 3 to 5 hours at an oven temperature of 60 to 90°C, set the vacuum kneader heating temperature to 40 to 60°C, and preheat for 2 to 4 hours. Add the preheated blend A, ground and dispersed resin D, and diluent to the preheated vacuum kneader, and vacuum knead for 10 to 30 minutes to obtain the matrix resin of the lightweight lightning protection surface film for composite materials with self-repairing function. The material temperature is controlled at 50 to 60°C, and the vacuum degree is controlled at -0.098MPa to -0.095MPa.

[0029] (5) The matrix resin of the lightweight lightning protection surface film for composite materials with self-repairing function and the flexible conductive polymer mesh are calendered and compounded on a double-roll calendering device to obtain an uncured lightweight lightning protection surface film for composite materials with self-repairing function, wherein the temperature of the coating roller of the double-roll hot calendering machine is controlled at 50-60°C.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention first synthesizes a tetrafunctional glycidylamine containing a dynamic disulfide bond, and prepares a lightweight lightning protection surface film for composite materials with self-repairing function by controlling the structure and proportion of the glycidylamine containing a dynamic disulfide bond, the composition and surface state of the lightweight conductive filler, the structure of the flexible conductive polymer network, the structure of the acid anhydride curing agent, and the structure and proportion of the toughening agent. The present invention designs and synthesizes a glycidylamine containing a dynamic disulfide bond, introduces the dynamic disulfide bond into the resin structure, and gives the modified resin system an intrinsic self-repairing feature; utilizes the curing reaction between the acid anhydride curing agent and the epoxy group to generate an ester bond, and the ester bond and the dynamic disulfide bond synergistically reduce the exchange activation energy of the dynamic covalent bond of the surface film during the repair process, thereby improving the self-repairing efficiency; introduces a plasma-treated lightweight conductive filler into the resin system of the surface film to improve the conductivity of the matrix resin and the intrinsic strength and toughness of the surface film; uses a flexible polymer network as a conductive network, which can improve the bending resistance of the surface film and reduce the weight of the surface film. The combination and synergy of the above design ideas together endow the composite material lightning protection surface film of the present invention with light weight and multiple self-repairing properties. In addition, based on the above synergistic method, the prepared composite material with self-repairing function has the advantages of excellent bonding performance, high hardness, and light weight. Its bonding strength is ≥25MPa, and the repair efficiency is ≥90%. Under the same functional conditions, the unit area weight can be reduced by more than 30%. DETAILED DESCRIPTION

[0032] The present invention is described in detail below with reference to specific embodiments, but is not limited thereto, and any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention.

[0033] Example 1

[0034] A method for preparing a lightweight lightning protection surface film for a composite material with a self-repairing function. The components of the lightweight lightning protection surface film for a composite material with a self-repairing function include glycidylamine containing dynamic covalent bonds, a diluent, an acid anhydride curing agent, an inorganic filler, a lightweight conductive filler, a flexible conductive polymer mesh and a toughening agent. The lightweight lightning protection surface film for a composite material with a self-repairing function is prepared by blending the components, mechanically dispersing, vacuum kneading, and hot calendering film-forming methods.

[0035] Furthermore, the glycidylamine containing a dynamic covalent bond is a glycidylamine containing a dynamic disulfide bond.

[0036] Furthermore, the glycidylamine molecules containing dynamic disulfide bonds include substances represented by structural formulas Ⅰ to Ⅳ:

[0037]

[0038]

[0039] Furthermore, the mass ratio of the glycidylamine containing dynamic disulfide bonds shown in structural formulas Ⅰ, Ⅱ, Ⅲ and Ⅳ is 100:5:10:5.

[0040] Furthermore, the diluent is a commercial reactive diluent containing epoxy groups, including diluent 622 (1,4-butanediol diglycidyl ether), 669 (ethylene glycol diglycidyl ether) and 690 (phenyl glycidyl ether), the mass ratio of the three is 1:1.2:1.2, and the amount of the diluent is 10% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0041] Furthermore, the anhydride curing agent includes phthalic anhydride and tetrabromophthalic anhydride in a mass ratio of 1:1; and the molar ratio of the anhydride curing agent to the epoxy groups in the formula components is 0.45:1.

[0042] Furthermore, the inorganic filler includes glass flakes and two-dimensional boron nitride nanosheets, and the mass ratio of glass flakes to two-dimensional boron nitride nanosheets is 100:10. The diameter of the glass flakes ranges from 0.1 mm to 0.5 mm, and the thickness ranges from 1 μm to 10 μm. The diameter of the two-dimensional boron nitride nanosheets ranges from 1 μm to 5 μm, and the thickness ranges from 2 nm to 10 nm. The amount of the inorganic filler is 5% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0043] Furthermore, the light conductive filler is composed of graphene, conductive carbon black and conductive carbon nanotubes, the light conductive filler is treated with plasma, the mass ratio of graphene, conductive carbon black and carbon nanotubes is 100:10:5, and the amount of the light conductive filler is 1% of the total mass of glycidylamine containing dynamic disulfide bonds.

[0044] Furthermore, the flexible conductive polymer mesh is a nylon fabric with a metal plated surface, the plated metal is silver, and the mass per unit area of ​​the plated metal is 50 g / ㎡.

[0045] Furthermore, the toughening agent comprises polyphenol oxide resin, polyether ketone resin and methyl methacrylate-butadiene-styrene copolymer, the mass ratio of polyphenol oxide resin, polyether ketone resin and methyl methacrylate-butadiene-styrene copolymer is 1:10:15, and the amount of the toughening agent is 10% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0046] Furthermore, the synthesis method of the tetrafunctional glycidylamine containing dynamic disulfide bonds comprises the following steps:

[0047] Add epichlorohydrin, deionized water and ethylene glycol to a four-necked flask equipped with a stirrer, a condensing device, a dropping funnel and nitrogen protection, heat the oil bath to 40°C, add 4,4'-diaminodiphenyl disulfide in three times, and after the addition, control the temperature of the reaction system at 50°C for 1h, then add chloroform and continue stirring for 6h. Lower the temperature to 30°C, slowly and uniformly add a 30% NaOH aqueous solution, and keep warm for 60min. After the reaction is completed, cool the reaction mixture to room temperature, add chloroform to the four-necked flask, transfer the reaction solution to a separatory funnel, and wash with deionized water 3 times; after standing and stratifying, take the lower layer solution to a beaker, add anhydrous MgSO 4 , stirred for 1 h; filtered to remove MgSO 4 After the solvent is removed by distillation, the product is separated and purified by silica gel column chromatography, with dichloromethane as the eluent. After the eluent is removed by distillation, it is dried in vacuo for 12 hours to obtain a tetrafunctional glycidylamine containing a dynamic disulfide bond, as shown in structural formula I. Among them, the molar ratio of 4,4'-diaminodiphenyl disulfide to epichlorohydrin is 1:2; epichlorohydrin, deionized water and ethylene glycol are mixed in any proportion; the ratio of epichlorohydrin to NaOH aqueous solution is 1mol:100ml; the ratio of chloroform to epichlorohydrin added twice is 5ml:1ml; epichlorohydrin and MgSO 4 The ratio is 1ml:3g.

[0048] Furthermore, the specific steps of preparing a lightweight lightning protection surface film for a composite material with self-repairing function by blending, mechanically dispersing, vacuum kneading, and hot calendering film-forming methods are as follows:

[0049] (1) Preparation of blends

[0050] The toughening agent and the tetrafunctional glycidylamine containing dynamic disulfide bonds shown in structural formula I are added to a chloroform solution, stirred until dissolved and transparent, and the chloroform is removed by rotary distillation to obtain a blend A of the toughening agent and the tetrafunctional glycidylamine containing dynamic disulfide bonds.

[0051] (2) Preparation of lightweight conductive filler and glycidylamine blends

[0052] The light conductive filler is added to the chloroform solution, ultrasonically dispersed for 1 hour, and the glycidylamine containing dynamic disulfide bonds shown in structural formula II to structural formula IV is added, and magnetic stirring is performed for 1 hour to form a uniform system. The chloroform is removed by rotary distillation to obtain a blend B of the light conductive filler and glycidylamine.

[0053] (3) Preparation of grinding dispersion resin

[0054] A blend B of a light conductive filler and glycidylamine, an anhydride curing agent and an inorganic filler are mixed to form a coarse mixture C, and the coarse mixture C is ground and dispersed three times on a CNC three-roll mill to obtain a ground and dispersed resin D. The roller surface temperature of the three-roll mill is controlled at 20°C.

[0055] (4) Preheat blend A in a blast drying oven for 3 h at an oven temperature of 60 °C, set the vacuum kneader heating temperature to 40 °C, and preheat for 2 h. Add the preheated blend A, grinding and dispersing resin D, and diluent to the preheated vacuum kneader, and vacuum knead for 10 min to obtain the matrix resin of the lightweight lightning protection surface film for composite materials with self-repairing function. The material temperature is controlled at 50 °C and the vacuum degree is controlled at -0.098 MPa.

[0056] (5) The matrix resin of the lightweight lightning protection surface film for the composite material with self-repairing function and the flexible conductive polymer mesh are calendered and compounded on a double-roll calendering device to obtain an uncured lightweight lightning protection surface film for the composite material with self-repairing function, wherein the temperature of the coating roller of the double-roll hot calendering machine is controlled at 50°C.

[0057] The lightweight lightning protection surface film for composite materials with self-repairing function prepared by the above steps has the advantages of excellent bonding performance, high hardness and light weight. Its shear strength is 26.0MPa and the crack repair efficiency is 90%. Under the same functional conditions, the mass per unit area can be reduced by 30%.

[0058] Example 2

[0059] A method for preparing a lightweight lightning protection surface film for a composite material with a self-repairing function. The components of the lightweight lightning protection surface film for a composite material with a self-repairing function include glycidylamine containing dynamic covalent bonds, a diluent, an acid anhydride curing agent, an inorganic filler, a lightweight conductive filler, a flexible conductive polymer mesh and a toughening agent. The lightweight lightning protection surface film for a composite material with a self-repairing function is prepared by blending the components, mechanically dispersing, vacuum kneading, and hot calendering film-forming methods.

[0060] Furthermore, the glycidylamine containing a dynamic covalent bond is a glycidylamine containing a dynamic disulfide bond.

[0061] Furthermore, the glycidylamine molecules containing dynamic disulfide bonds include substances represented by structural formulas Ⅰ to Ⅳ:

[0062]

[0063] Furthermore, the mass ratio of the glycidylamine containing dynamic disulfide bonds shown in structures Ⅰ, Ⅱ, Ⅲ and Ⅳ is 100:15:20:10.

[0064] Furthermore, the diluent is a commercial reactive diluent containing epoxy groups, including diluent HK-66 (alkylene glycidyl ether), X-632 (polypropylene glycol diglycidyl ether) and AGE (C12-14 fatty glycidyl ether), the ratio of the three is 1:1.2:1.3, and the amount of the diluent is 20% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0065] Furthermore, the anhydride curing agent includes phthalic anhydride, glutaric anhydride and maleic anhydride, and the ratio of the three is 1:0.5:0.1. The molar ratio of the anhydride curing agent to the epoxy group in the formula components is 0.5:1.

[0066] Furthermore, the inorganic filler includes glass flakes and two-dimensional boron nitride nanosheets, and the mass ratio of glass flakes to two-dimensional boron nitride nanosheets is 100:50. The diameter of the glass flakes ranges from 0.1 mm to 0.5 mm, and the thickness ranges from 1 μm to 10 μm. The diameter of the two-dimensional boron nitride nanosheets ranges from 1 μm to 5 μm, and the thickness ranges from 2 nm to 10 nm. The amount of the inorganic filler is 15% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0067] Furthermore, the lightweight conductive filler is composed of graphene, conductive carbon black and conductive carbon nanotubes, the lightweight conductive filler is treated with plasma, the mass ratio of graphene, conductive carbon black and carbon nanotubes is 100:20:15, and the amount of the lightweight conductive filler is 5% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0068] Furthermore, the flexible conductive polymer mesh is a polyester fabric with a metal plated surface, the plated metal is copper, and the mass per unit area is 100 g / ㎡.

[0069] Furthermore, the toughening agent comprises polyetherketone resin and methyl methacrylate-butadiene-styrene copolymer, the ratio of the two is 1:0.8, and the amount of the toughening agent is 20% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0070] Furthermore, the synthesis method of the tetrafunctional glycidylamine containing dynamic disulfide bonds comprises the following steps:

[0071] Epichlorohydrin, deionized water and ethylene glycol were added to a four-necked flask equipped with a stirrer, a condensing device, a dropping funnel and nitrogen protection. The oil bath was heated to 60°C, and 4,4'-diaminodiphenyl disulfide was added in 5 times. After the addition, the temperature of the reaction system was controlled at 70°C for 2 hours, and then chloroform was added. The stirring reaction was continued for 10 hours. The temperature was lowered to 50°C, and a 50% NaOH aqueous solution was slowly and uniformly added, and the temperature was kept for 150 minutes. After the reaction was completed, the reaction mixture was cooled to room temperature and chloroform was added to the four-necked flask. The reaction solution was transferred to a separatory funnel and washed with deionized water 5 times. After standing and stratification, the lower layer solution was taken to a beaker and anhydrous MgSO was added. 4 , stirred for 3 h; filtered to remove MgSO 4 After the solvent is distilled off, the product is separated and purified by silica gel column chromatography, with dichloromethane as the eluent. After the eluent is distilled off, it is vacuum dried for 24 hours to obtain a tetrafunctional glycidylamine containing a dynamic disulfide bond, as shown in structural formula I. Among them, the molar ratio of 4,4'-diaminodiphenyl disulfide to epichlorohydrin is 1:2; epichlorohydrin, deionized water and ethylene glycol are mixed in any proportion; the ratio of epichlorohydrin to NaOH aqueous solution is 1mol:200ml; the ratio of chloroform to epichlorohydrin added twice is 15ml:1ml; epichlorohydrin and MgSO 4 The ratio is 1ml:6g.

[0072] Furthermore, the specific steps of preparing a lightweight lightning protection surface film for a composite material with self-repairing function by blending, mechanically dispersing, vacuum kneading, and hot calendering film-forming methods are as follows:

[0073] (1) Preparation of blends

[0074] The toughening agent and the tetrafunctional glycidylamine containing dynamic disulfide bonds shown in structural formula I are added to a chloroform solution, stirred until dissolved and transparent, and the chloroform is removed by rotary distillation to obtain a blend A of the toughening agent and the tetrafunctional glycidylamine containing dynamic disulfide bonds.

[0075] (2) Preparation of lightweight conductive filler and glycidylamine blends

[0076] The light conductive filler was added to the chloroform solution, ultrasonically dispersed for 3 hours, and glycidylamine containing dynamic disulfide bonds shown in structural formula II to structural formula IV was added, and magnetic stirring was performed for 3 hours to form a uniform system. The chloroform was removed by rotary distillation to obtain a light conductive filler and glycidylamine blend B.

[0077] (3) Preparation of grinding dispersion resin

[0078] A blend B of a light conductive filler and glycidylamine, an anhydride curing agent and an inorganic filler are mixed to form a coarse mixture C, and the coarse mixture C is ground and dispersed on a CNC three-roll mill for 5 times to obtain a ground and dispersed resin D. The roller surface temperature of the three-roll mill is controlled at 50°C.

[0079] (4) Preheat blend A in a blast drying oven for 5 h at an oven temperature of 90 °C, set the vacuum kneader heating temperature to 60 °C, and preheat for 4 h. Add the preheated blend A, grinding and dispersing resin D, and diluent to the preheated vacuum kneader, and vacuum knead for 30 min to obtain the matrix resin of the lightweight lightning protection surface film for composite materials with self-repairing function. The material temperature is controlled at 60 °C and the vacuum degree is controlled at -0.095 MPa.

[0080] (5) The matrix resin of the lightweight lightning protection surface film for the composite material with self-repairing function and the flexible conductive polymer mesh are calendered and compounded on a double-roll calendering device to obtain an uncured lightweight lightning protection surface film for the composite material with self-repairing function, wherein the temperature of the coating roller of the double-roll hot calendering machine is controlled at 60°C.

[0081] The lightweight lightning protection surface film for composite materials with self-repairing function prepared by the above steps has the advantages of excellent bonding performance, high hardness and light weight. Its shear strength is 25.2MPa and crack repair efficiency is 91%. Under the same functional conditions, the mass per unit area can be reduced by 31%.

[0082] Example 3

[0083] A method for preparing a lightweight lightning protection surface film for a composite material with a self-repairing function. The components of the lightweight lightning protection surface film for a composite material with a self-repairing function include glycidylamine containing dynamic covalent bonds, a diluent, an acid anhydride curing agent, an inorganic filler, a lightweight conductive filler, a flexible conductive polymer mesh and a toughening agent. The lightweight lightning protection surface film for a composite material with a self-repairing function is prepared by blending the components, mechanically dispersing, vacuum kneading, and hot calendering film-forming methods.

[0084] Furthermore, the glycidylamine containing a dynamic covalent bond is a glycidylamine containing a dynamic disulfide bond.

[0085] Furthermore, the glycidylamine molecules containing dynamic disulfide bonds include substances represented by structural formulas Ⅰ to Ⅳ:

[0086]

[0087] Furthermore, the mass ratio of the glycidylamine containing dynamic disulfide bonds shown in structural formulas Ⅰ, Ⅱ, Ⅲ and Ⅳ is 100:10:15:7.5.

[0088] Furthermore, the diluent is a commercial reactive diluent containing epoxy groups, including diluent 622 (1,4-butanediol diglycidyl ether), X-632 (polypropylene glycol diglycidyl ether) and D-691 propylene oxide o-tolyl ether, the ratio of the three is 1:0.4:0.2, and the amount of the diluent is 15% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0089] Furthermore, the anhydride curing agent includes diphenyl ether tetracarboxylic dianhydride and maleic anhydride, and the ratio of the two is 1:0.5; the molar ratio of the anhydride curing agent to the epoxy group in the formula components is 0.47:1.

[0090] Furthermore, the inorganic filler includes glass flakes and two-dimensional boron nitride nanosheets, and the mass ratio of glass flakes to two-dimensional boron nitride nanosheets is 100:30. The diameter of the glass flakes ranges from 0.1 mm to 0.5 mm, and the thickness ranges from 1 μm to 10 μm. The diameter of the two-dimensional boron nitride nanosheets ranges from 1 μm to 5 μm, and the thickness ranges from 2 nm to 10 nm. The amount of the inorganic filler is 10% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0091] Furthermore, the light conductive filler is composed of graphene, conductive carbon black and conductive carbon nanotubes, the light conductive filler is treated with plasma, the mass ratio of graphene, conductive carbon black and carbon nanotubes is 100:15:10, and the amount of the light conductive filler is 3% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0092] Furthermore, the flexible conductive polymer mesh is a nylon fabric with a metal plated on the surface, the plated metal is a mixture of silver and copper, the mass ratio of silver to copper is 1:0.5, and the mass per unit area of ​​the plated metal is 75g / ㎡.

[0093] Furthermore, the toughening agent comprises polyphenol oxide resin and methyl methacrylate-butadiene-styrene copolymer, the mass ratio of the two is 1:0.2, and the amount of the toughening agent is 15% of the total mass of the glycidylamine containing dynamic disulfide bonds.

[0094] Furthermore, the synthesis method of the tetrafunctional glycidylamine containing dynamic disulfide bonds comprises the following steps:

[0095] Epichlorohydrin, deionized water and ethylene glycol were added to a four-necked flask equipped with a stirrer, a condensing device, a dropping funnel and nitrogen protection. The oil bath was heated to 50°C, and 4,4'-diaminodiphenyl disulfide was added in four portions. After the addition, the temperature of the reaction system was controlled at 60°C for 1.5 hours, and then chloroform was added. The stirring reaction was continued for 8 hours. The temperature was lowered to 40°C, and a 40% NaOH aqueous solution was slowly and uniformly added, and the temperature was kept for 105 minutes. After the reaction was completed, the reaction mixture was cooled to room temperature and chloroform was added to the four-necked flask. The reaction solution was transferred to a separatory funnel and washed with deionized water 4 times. After standing and stratification, the lower layer solution was taken to a beaker and anhydrous MgSO was added. 4 , stirred for 2 h; filtered to remove MgSO 4 After the solvent is removed by distillation, the product is separated and purified by silica gel column chromatography, with dichloromethane as the eluent. After the eluent is removed by distillation, it is dried in vacuo for 18 hours to obtain a tetrafunctional glycidylamine containing a dynamic disulfide bond, as shown in structural formula I. Among them, the molar ratio of 4,4'-diaminodiphenyl disulfide to epichlorohydrin is 1:2; epichlorohydrin, deionized water and ethylene glycol are mixed in any proportion; the ratio of epichlorohydrin to NaOH aqueous solution is 1mol:150ml; the ratio of chloroform to epichlorohydrin added twice is 10ml:1ml; epichlorohydrin and MgSO 4 The ratio is 1ml:4.5g.

[0096] Furthermore, the specific steps of preparing a lightweight lightning protection surface film for a composite material with self-repairing function by blending, mechanically dispersing, vacuum kneading, and hot calendering film-forming methods are as follows:

[0097] (1) Preparation of blends

[0098] The toughening agent and the tetrafunctional glycidylamine containing dynamic disulfide bonds shown in structural formula I are added to a chloroform solution, stirred until dissolved and transparent, and the chloroform is removed by rotary distillation to obtain a blend A of the toughening agent and the tetrafunctional glycidylamine containing dynamic disulfide bonds.

[0099] (2) Preparation of lightweight conductive filler and glycidylamine blends

[0100] The light conductive filler is added to the chloroform solution, ultrasonically dispersed for 2 hours, and the glycidylamine containing dynamic disulfide bonds shown in structural formula II to structural formula IV is added, and magnetic stirring is performed for 2 hours to form a uniform system. The chloroform is removed by rotary distillation to obtain a light conductive filler and glycidylamine blend B.

[0101] (3) Preparation of grinding dispersion resin

[0102] A blend B of a light conductive filler and glycidylamine, an anhydride curing agent and an inorganic filler are mixed to form a coarse mixture C, and the coarse mixture C is ground and dispersed on a CNC three-roll mill for four times to obtain a ground and dispersed resin D. The roller surface temperature of the three-roll mill is controlled at 35°C.

[0103] (4) Preheat blend A in a blast drying oven for 4 h at a temperature of 75 °C, set the vacuum kneader heating temperature to 50 °C, and preheat for 3 h. Add the preheated blend A, grinding and dispersing resin D, and diluent to the preheated vacuum kneader, and vacuum knead for 20 min to obtain the matrix resin of the lightweight lightning protection surface film for composite materials with self-repairing function. The material temperature is controlled at 55 °C and the vacuum degree is controlled at -0.0965 MPa.

[0104] (5) The matrix resin of the lightweight lightning protection surface film for the composite material with self-repairing function and the flexible conductive polymer mesh are calendered and compounded on a double-roll calendering device to obtain an uncured lightweight lightning protection surface film for the composite material with self-repairing function, wherein the temperature of the coating roller of the double-roll hot calendering machine is controlled at 55°C.

[0105] The lightweight lightning protection surface film for composite materials with self-repairing function prepared by the above steps has the advantages of excellent bonding performance, high hardness and light weight. Its shear strength is 25.6MPa and crack repair efficiency is 92%. Under the same functional conditions, the mass per unit area can be reduced by 32%.

Claims

1. A glycidylamine containing a dynamic disulfide bond, characterized in that: The molecular structure of the glycidylamine containing dynamic disulfide bonds includes substances represented by structural formula I, structural formula II, structural formula III or structural formula IV:

2. A method for preparing glycidylamine containing dynamic disulfide bonds, characterized in that: The method comprises the following steps: adding epichlorohydrin, deionized water and ethylene glycol to a four-necked flask equipped with a stirrer, a condensing device, a dropping funnel and nitrogen protection, heating the mixture in an oil bath at 40-60°C, adding 4,4'-diaminodiphenyl disulfide in 3-5 times, controlling the temperature of the reaction system at 50-70°C after the addition, reacting for 1-2 hours, adding chloroform, continuing to stir and react for 6-10 hours, lowering the temperature to 30-50°C, slowly and uniformly dropping a 30%-50% NaOH aqueous solution, and keeping the temperature for 60-150 minutes. After the reaction is completed, cooling the reaction mixture to room temperature, adding chloroform to the four-necked flask, transferring the reaction solution to a separating funnel, and washing with deionized water for several times; standing for stratification, taking the lower layer solution into a beaker, and adding anhydrous MgSO4 is added and stirred for 1 to 3 hours; MgSO4 is removed by filtration, and the product after the solvent is distilled off is separated and purified by silica gel column chromatography, using dichloromethane as the eluent, the eluent is distilled off, and vacuum dried to obtain a tetrafunctional glycidylamine with a dynamic disulfide bond, as shown in structural formula I of claim 1, wherein the molar ratio of 4,4'-diaminodiphenyl disulfide to epichlorohydrin is 1:2; epichlorohydrin, deionized water and ethylene glycol are mixed in any proportion; the ratio of epichlorohydrin to NaOH aqueous solution is 1 mol:100 to 200 ml; the ratio of chloroform to epichlorohydrin added twice is 5 ml to 15 ml:1 ml; the ratio of epichlorohydrin to MgSO4 is 1 ml:3 g to 6 g.

3. A method for preparing a lightweight lightning protection surface film for a composite material with self-repairing function, characterized in that: The components of the lightweight lightning protection surface film for composite materials with self-repairing function include glycidylamine containing dynamic disulfide bonds, a diluent, an acid anhydride curing agent, an inorganic filler, a lightweight conductive filler, a flexible conductive polymer network and a toughening agent. The components are prepared by blending, mechanical dispersion, vacuum kneading, and hot calendering film-forming methods to obtain a lightweight lightning protection surface film for composite materials with self-repairing function. The glycidylamine containing dynamic disulfide bonds includes the substances described in structural formulas I, II, III and IV described in claim 1.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the glycidylamine containing dynamic disulfide bonds shown in structural formula I, structural formula II, structural formula III and structural formula IV is 100:5-15:10-20:5-10.

5. The preparation method according to claim 3, characterized in that: The diluent is a commercial reactive diluent containing epoxy groups, including one or a mixture of alkylene glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, polypropylene glycol diglycidyl ether, C12-14 fatty glycidyl ether, benzyl glycidyl ether, 1,6-hexanediol diglycidyl ether and D-691 propylene oxide o-tolyl ether, and the amount of the diluent is 10% to 20% of the total mass of the glycidylamine containing dynamic disulfide bonds.

6. The preparation method according to claim 3, characterized in that: The anhydride curing agent includes one or a mixture of phthalic anhydride, tetrabromophthalic anhydride, diphenyl ether tetracarboxylic anhydride, succinic anhydride, glutaric anhydride and maleic anhydride, and the molar ratio of the anhydride curing agent to the epoxy groups in the formula components is 0.45-0.5:1; the inorganic filler includes glass flakes and two-dimensional boron nitride nanosheets, and the mass ratio of the glass flakes to the two-dimensional boron nitride nanosheets is 100:10-50, and the total amount of the inorganic filler is 5%-15% of the total mass of the glycidylamine containing dynamic disulfide bonds.

7. The preparation method according to claim 3, characterized in that: The light conductive filler comprises plasma functionalized graphene, plasma functionalized conductive carbon black and plasma functionalized carbon nanotubes, wherein the mass ratio of the plasma functionalized graphene, plasma functionalized conductive carbon black and plasma functionalized carbon nanotubes is 100:10-20:5-15, and the total amount of the light conductive filler is 1%-5% of the total mass of the glycidylamine containing dynamic disulfide bonds.

8. The preparation method according to claim 3, characterized in that: The flexible conductive polymer mesh is a nylon or polyester fabric with metal plated on the surface. The plated metal includes silver or copper or a mixture of silver and copper in any proportion or a silver-copper alloy in any proportion or a silver-nickel alloy with a mass ratio of 100:10 to 20. The mass per unit area of ​​the plated metal is in the range of 50g / ㎡ to 100g / ㎡.

9. The preparation method according to claim 3, characterized in that: The toughening agent comprises one or a mixture of polyphenol oxide resin, polysulfone resin, polyether ketone resin and methyl methacrylate-butadiene-styrene copolymer, and the amount of the toughening agent is 10%-20% of the total mass of the glycidylamine containing dynamic disulfide bonds.

10. The preparation method according to claim 3, characterized in that: The specific steps of preparing a lightweight lightning protection surface film for a composite material with self-repairing function by blending, mechanically dispersing, vacuum kneading, and hot calendering film-forming methods of the components are as follows: (1) Preparation of blends Adding a toughening agent and a tetrafunctional glycidylamine containing a dynamic disulfide bond as shown in structural formula I into a chloroform solution, stirring until dissolved and transparent, and removing the chloroform by rotary distillation to obtain a blend A of the toughening agent and the tetrafunctional glycidylamine containing a dynamic disulfide bond; (2) Preparation of lightweight conductive filler and glycidylamine blends The light conductive filler is added to the chloroform solution, and ultrasonically dispersed uniformly, and glycidylamine containing dynamic disulfide bonds shown in structural formula II to structural formula IV is added, and magnetic stirring is performed to form a uniform system, and chloroform is removed by rotary distillation to obtain a blend B of the light conductive filler and glycidylamine; (3) Preparation of grinding dispersion resin A blend B of a light conductive filler and glycidylamine, an anhydride curing agent and an inorganic filler are mixed to form a crude mixture C, and the crude mixture C is ground and dispersed on a CNC three-roll grinder for several times to obtain a ground and dispersed resin D; wherein the roller surface temperature of the three-roll grinder is controlled within a range of 20 to 50° C.; (4) preheating the blend A in a blast drying oven at a temperature of 60 to 90° C., setting the heating temperature of the vacuum kneader to 40 to 60° C., and preheating; adding the preheated blend A, the ground and dispersed resin D, and the diluent to the preheated vacuum kneader, and vacuum kneading for 10 to 30 minutes to obtain a matrix resin for a lightweight lightning protection surface film for a composite material with a self-repairing function, wherein the material temperature is controlled at 50 to 60° C., and the vacuum degree is controlled at -0.098 MPa to -0.095 MPa; (5) The matrix resin of the lightweight lightning protection surface film for the composite material with self-repairing function and the flexible conductive polymer mesh are calendered and compounded on a double-roll calendering device to obtain an uncured lightweight lightning protection surface film for the composite material with self-repairing function, wherein the temperature of the coating roller of the double-roll hot calendering machine is controlled at 50-60°C.